Pengaruh Metode Thawing terhadap Kualitas Semen Beku Sapi Bali, Sapi Madura dan Sapi PO - Muhammad Ade Salim; Trinil Susilawati; Sri Wahyuningsih (Agricultural Faculty, 2012)
Effect of thawing technique to quality frozen semen spermatozoa in bali, madura and PO cattleABSTRACT. The experiment was conducted from November 2011 to January 2012 in BBIB Singosari. The study aims was to determine the effect of thawing techniques on the quality frozen bovine sperm Bali, Madura and PO cattle. This material used 90 frozen straw of three cattle from the three breed. The method is an experiment with three treatments and 10 replications for frozen to thawing in temperature water is 5 0C of duration 60 seconds, 15 0C duration 30 seconds and 37 0C duration 15 seconds. Variables observed in this study were sperm quality are motility, viability and abnormality. Data in percentage transformed in to arcus sinus were analyzed using Completely Randomized Block Design (CRBD) with replication as blocks of 10x. The results showed the thawing at 37 0C duration 15 seconds to highly significant effect (P0,01) viability and motility and significant effect (P0.05). The abnormalities, no significant effect (P0,05). Breed cattle not significant effect to quality. It can be concluded that thawing techniques impact the motility and viability in frozen bovine semen spermatozoa Bali, Madura and PO cattle. Thawing using 37 0C temperature water with duration of 15 seconds is the best method to obtain the quality of spermatozoa post thawing frozen sperm.